Isolation of acetylcholinesterase G4 and G1 molecular isoforms from rat cortex. - ZHAO Qin; TANG Xi-Can (Acta Pharmacologica Sinica, 2016)
AIM: To isolate the G4 and G1 molecular forms of acetylcholinesterase in rat cortex for interpreting the therapeutical effect of the AChE inhibitor drugs. METHODS: Size exclusion chromatography and ultracentrifugation were used to isolate and ascertain the G4 and G1 molecular forms of AChE. RESULTS: After size exclusion chromatography, two AChE active peaks were gotten. The putative molecular weights of the two highest AChE active fractions were around Mr 239 000 and Mr 68 000 respectively, which represented G4 and G1 AChE isoforms. The sedimentation coefficients of the Mr 239 000 and Mr 68 000 fractions were 10 S and 4 S, which also assigned to G4 and G1 AChE isoforms. CONCLUSION: The G4 and G1 isoforms of AChE could be gotten by size exclusion chromatography method.